Gender inequality: African feminist fiction reflecting scientific data (2013)
When one mentions the situation of women anywhere in the world today, certain issues inevitably come to mind. Issues such as oppression of women, feminism and women's struggle for liberation, woman as liberated-subaltern in organisations, sexuality and sexism, among others. These are issues that have often trailed humanity. Available answers do not yet adequately address the woman question. We are in a complex situation, a complex world that smacks of gender war in the midst of gendered rhetoric. The matter of Sub-Saharan African women's evolution calls to mind immense, complex and culturally multifarious questions that surround women in the region and the fast changing world of African culture, relating to issues of family, education, work and lifestyle. The compass of women development in the region is therefore multidirectional. This necessitates knowing her pre-colonial past, her colonial status and her post- or neo-colonial condition. This paper therefore looks at the African woman under the three stages above, with particular attention on the Nigerian woman of today.